A review on contemporary nanomaterial-based therapeutics for the treatment of diabetic foot ulcers (DFUs) with special reference to the Indian scenario. Issue 11 (20th April 2022) - Sethuram, Lakshimipriya; Thomas, John; Mukherjee, Amitava; Chandrasekaran, Natarajan
Abstract : Nanomaterial-based therapeutic treatment shows promising results in enhancing the anti-inflammatory, antimicrobial and angiogenic potential in diabetic rodents for effective wound healing process. Abstract : Diabetes mellitus (DM) is a predominant chronic metabolic syndrome, resulting in various complications and high mortality associated with diabetic foot ulcers (DFUs). Approximately 15–30% of diabetic patients suffer from DFUs, which is expected to increase annually. The major challenges in treating DFUs are associated with wound infections, alterations to inflammatory responses, angiogenesis and lack of extracellular matrix (ECM) components. Furthermore, the lack of targeted therapy and efficient wound dressings for diabetic wounds often results in extended hospitalization and limb amputations. Hence, it is essential to develop and improve DFU-specific therapies. Nanomaterial-based innovative approaches have tremendous potential for preventing and treating wound infections of bacterial origin. They have greater benefits compared to traditional wound dressing approaches. In this approach, the physiochemical features of nanomaterials allow researchers to employ different methods for diabetic wound healing applications. In this review, the status and prevalence of diabetes mellitus (DM) and amputations due to DFUs in India, the pathophysiology of DFUs and their complications are discussed. Additionally, nanomaterial-based approaches such as the use of nanoemulsions, nanoparticles, nanoliposomes and nanofibers for the treatment of DFUs are studied. Besides, emerging therapeutics such as bioengineered skin substitutes and nanomaterial-based innovative approaches such as antibacterial hyperthermia therapy and gene therapy for the treatment of DFUs are highlighted. The present nanomaterial-based techniques provide a strong base for future therapeutic approaches for skin regeneration strategies in the treatment of diabetic wounds.